Building strong brand image in the smartphone industry: the interplay of brand familiarity, brand awareness, and brand extension - Kamal, Nabila Salwa; Agesta, Tirani; Deduu, May (Jurnal Mantik, 2025)
This research examines the influence of brand familiarity, brand awareness, and brand extension on the overall perception of brand image. The study emphasizes the experiences and viewpoints of smartphone users across different brands to investigate how these three factors collectively shape a strong brand image in consumers' minds. This study employs a quantitative approach, utilizing primary data collected through online surveys. The sample comprises 160 respondents who are users of various smartphone brands in Cirebon, selected through a purposive convenience sampling method. The study applies the Structural Equation Modeling - Partial Least Square (SEM-PLS) technique to analyze the relationship between the examined variables. The findings reveal that brand familiarity and awareness significantly and positively impact brand image. Furthermore, brand extension also plays a crucial role in enhancing brand image. These findings confirm that these three variables are significant in shaping consumer perceptions of a brand. The practical implications of this study emphasize the importance of companies developing marketing strategies that are oriented towards increasing brand familiarity and awareness as well as the effectiveness of brand extension. By optimally managing these aspects, companies can build a strong and positive brand image, which ultimately contributes to increasing consumer trust and loyalty towards the smartphone products they offer